A qualitative exploration of cognitive and sociocultural influences on postoperative pain among urological patients in Ghana - Linda Hayford; Prof. Lydia Aziato; Prof. Matthew Yamoah Kyei (Elsevier, 2023)
Background: Patients ascribe diverse meanings to postoperative pain (POP), usually based on personal beliefs. However, patients' perceptions about the causes of pain are usually influenced by their traditional beliefs and misconceptions, and cultural factors such as ethnic background serve as barriers to effective pain control. The study sought to explore the cognitive and sociocultural aspects of postoperative pain experience after urological surgeries. Methods: The study employed exploratory descriptive qualitative research design. Twelve male participants who had undergone urological surgery in a teaching hospital were recruited using purposive sampling. Data were collected through individual face-to-face in-depth interviews, conducted in English and Akan languages. The interviews were audio-taped and transcribed verbatim. Ethical considerations such as informed consent, anonymity, and confidentiality were ensured. Concurrent data analysis was done engaging the processes of content analysis. Findings: Cognitive aspects of the POP revealed three themes; the knowledge of the pain, attitude, and beliefs of the patients, and meanings the patients ascribed to the pain. Similarly, sociocultural aspects revealed two emerging themes; the family dynamics and roles influencing pain experience, and individual cultural background and belief systems. The participants' diverse views and experiences influenced their pain expression and experience after urological surgery. Conclusions: Postoperative pain is a multidimensional experience and includes socio-cultural and cognitive aspects. Therefore, contemporary pain management strategies should focus on client-centered and culturally sensitive interventions.